In vitro and in vivo efficacy of Monepantel (AAD 1566) against laboratory models of human intestinal nematode infections. - Lucienne Tritten; Angelika Silbereisen; Jennifer Keiser (Public Library of Science (PLoS), 2011)
BACKGROUND: Few effective drugs are available for soil-transmitted helminthiases and drug resistance is of concern. In the present work, we tested the efficacy of the veterinary drug monepantel, a potential drug development candidate compared to standard drugs in vitro and in parasite-rodent models of relevance to human soil-transmitted helminthiases. METHODOLOGY: A motility assay was used to assess the efficacy of monepantel, albendazole, levamisole, and pyrantel pamoate in vitro on third-stage larvae (L3) and adult worms of Ancylostoma ceylanicum, Necator americanus and Trichuris muris. Ancylostoma ceylanicum- or N. americanus-infected hamsters, T. muris- or Ascaris suum-infected mice, and Strongyloides ratti-infected rats were treated with single oral doses of monepantel or with one of the reference drugs. PRINCIPAL FINDINGS: Monepantel showed excellent activity on A. ceylanicum adults (IC(50) = 1.7 µg/ml), a moderate effect on T. muris L3 (IC(50) = 78.7 µg/ml), whereas no effect was observed on A. ceylanicum L3, T. muris adults, and both stages of N. americanus. Of the standard drugs, levamisole showed the highest potency in vitro (IC(50) = 1.6 and 33.1 µg/ml on A. ceylanicum and T. muris L3, respectively). Complete elimination of worms was observed with monepantel (10 mg/kg) and albendazole (2.5 mg/kg) in A. ceylanicum-infected hamsters. In the N. americanus hamster model single 10 mg/kg oral doses of monepantel and albendazole resulted in worm burden reductions of 58.3% and 100%, respectively. Trichuris muris, S. ratti and A. suum were not affected by treatment with monepantel in vivo (following doses of 600 mg/kg, 32 mg/kg and 600 mg/kg, respectively). In contrast, worm burden reductions of 95.9% and 76.6% were observed following treatment of T. muris- and A. suum infected mice with levamisole (200 mg/kg) and albendazole (600 mg/kg), respectively. CONCLUSIONS/SIGNIFICANCE: Monepantel reveals low or no activities against N. americanus, T. muris, S. ratti and A. suum in vivo, hence does not qualify as drug development candidate for human soil-transmitted helminthiases.